Associations between canine temperament and salivary concentrations of cortisol and serotonin - Youngwook Jung; Yujin Song; Kayoung Yang; Kyongwon Yoo; Youngtae Heo; Minjung Yoon (PLoS ONE, 2026)
Temperament influences canine behavior and helps determine a dog’s suitability as a companion or working animal. Although several temperament assessments exist, many rely on subjective evaluations, highlighting the need for scientifically validated methods. This study evaluated the validity of the Wesen temperament test by examining its association with physiological biomarkers—salivary cortisol and serotonin. Twenty-four dogs (11 females and 13 males) completed a modified Wesen test comprising seven subtests: Unconscious Confidence, Sociality, Noise Stability, Movement Stability, Desire for Play and Predation, Behavior in Stressful Situations, and Separation. Saliva samples were collected pre- and post-assessment, and cortisol and serotonin concentrations were measured using ELISA. Hormonal concentrations and temperament scores were analyzed using correlation, regression, and Kruskal-Wallis tests. Pre-assessment cortisol concentrations were negatively correlated with total average temperament score and several subtest scores. Post-assessment cortisol concentrations showed significant negative correlations with total average scores and all subtests. Changes in cortisol concentrations from pre- to post-assessment were negatively associated with temperament scores. Dogs with higher temperament scores exhibited significantly higher serotonin concentrations than those with lower scores. These results support the utility of temperament assessments validated through physiological markers and provide novel evidence linking canine temperament with endocrine function.